Improving Oral Hygiene Maintenance Through Teacher Empowerment to Reduce the Debris Index of Children with Disabilities - Silvia Prasetyowati; Isnanto Isnanto; Aprilinda Pipit R (International Journal of Advanced Health Science and Technology, 2023)
The prevalence of disability continues to increase. In 2003 there were 0.9% of all children in Indonesia with disabilities, in 2006 there were 1.38% of all children in Indonesia with disabilities and the peak in 2012 was 2.45% of all children in Indonesia. Children with disabilities are vulnerable and prone to exposure to diseases and threats. According to the 2011 Social Protection Programme (PPLS), there were 32,990 children with disabilities from poor families. Disability is defined as the physical inability of the body to perform normal bodily functions. Teacher empowerment is very important because through teacher empowerment, teachers will gain new knowledge, new ideas in achieving the learning process. Through teacher empowerment activities on the importance of maintaining oral hygiene in students with disabilities will motivate teachers to further increase the importance of maintaining oral hygiene in students with disabilities. This study is to analyse the effect of improving oral hygiene maintenance through teacher empowerment on reducing the debris index of children with disabilities. The type of research used is Analytical Quasi Experiment. The targets in the study were all SLB D/YPAC teachers. Data collection methods using questionnaires and observation. Data analysis technique using chi square  statistical test. The  results of the  study showed that there was an effect of knowledge  and attitude of maintaining oral hygiene through teacher empowerment on reducing the debris index of children in SLB-D YPAC Surabaya.